Lifecycle impacts of the financial and economic crisis on household optimal consumption, portfolio choice, and labor supply - Jingjing Chai; Raimond H. Maurer; Olivia S. Mitchell; Ralph Rogalla (Goethe University Frankfurt, Center for Financial Studies (CFS), 2011)
The direct financial impact of the financial crisis has been to deal a heavy blow to investment-based pensions; many workers lost a substantial portion of their retirement saving. The financial sector implosion produced an economic crisis for the rest of the economy via high unemployment and reduced labor earnings, which reduced household contributions to Social Security and some private pensions. Our research asks which types of individuals were most affected by these dual financial and economic shocks, and it also explores how people may react by changing their consumption, saving and investment, work and retirement, and annuitization decisions. We do so with a realistically calibrated lifecycle framework allowing for time-varying investment opportunities and countercyclical risky labor income dynamics. We show that households near retirement will reduce both short- and long-term consumption, boost work effort, and defer retirement. Younger cohorts will initially reduce their work hours, consumption, saving, and equity exposure; later in life, they will work more, retire later, consume less, invest more in stocks, save more, and reduce their demand for private annuities.
urn:nbn:de:hebis:30-115892
Keywords: D1; G11; G23; G35; J14; J26; J32; 330; Financial Crisis; Household Finance; Life Cycle Portfolio Choice; Labor Supply; Wirtschaftskrise; Lebenszyklus; Arbeitslosigkeit; Einkommen; Konsum; Sparen; Alterssicherung; Theorie